Attitude of poultry farmers towards vaccination against newcastle disease and avian influenza in Ibadan, Nigeria (2012)
Newcastle disease (ND) and Avian Influenza (AI) are among the important viral diseases of poultry with very high economic implications. ND is enzootic in most parts of the world while Highly Pathogenic AI (HPAI) is an emerging zoonosis in Nigeria. This study was carried out to assess the perception and attitude of poultry farmers in the selected Local Government Areas in Ibadan towards vaccination of birds against these diseases, and to find out the types of vaccines that were available for the control of the two diseases. A total of 84 respondents out of 100 (84%) completed and returned the questionnaires administered. The results indicated that all farmers vaccinated their birds against ND. The regime for ND vaccination was not the same across the local government areas. Some 32 (38.1%) farmers operated vaccination schedules provided by hatchery technicians, while 43 (51.2%) farmers vaccinated their birds at about 4-6 weeks interval. Nine (10.7%) farmers combined hatchery and laboratory evaluation to determine schedule. Thirty nine farmers (46.4%) indicated that they were aware of national policy of non-vaccination against AI. However, 14 out of 84 farmers (16.7%) vaccinated their birds against HPAI. There is a need to continue the national policy of slaughter of HPAI infected poultry birds and compensation of farmers, albeit allowing strategic use of vaccine to effectively control HPAI outbreaks in south-western part of Nigeria.